A new species of Pseudione Kossmann, 1881 (Crustacea, Isopoda, Bopyridae) parasitizing the squat lobster Munida microphthalma A. Milne-Edwards, 1880 in the Southwestern Atlantic - Brito, Ayrton; Cardoso, Irene Azevedo; Boyko, Christopher B. (Zootaxa, 2018)
A new species of Pseudione Kossmann, 1881, is described from 21 parasitized individuals of the squat lobster Munida microphthalma A. Milne-Edwards, 1880, collected in Brazilian waters of the southwestern Atlantic Ocean. The new species belongs to the Pseudione “crénéles” group sensu Bourdon (1976). The number of specimens obtained as well as the life history stage diversity of the type series, consisting of mature females, mature males, subadult males and cryptoniscus larvae, are unusually large for bopyrid isopod type series.